Benjamin West and his cat Grimalkin - Henry, Marguerite, 1902-1997; Dennis, Wesley (New York : Aladdin, 2014)
With his beloved black cat Grimalkin as his constant companion, the young Quaker boy Benjamin West discovers and develops his talent as an artist.
Originally published: 1947.
Ages 8-12.
Keywords: West, Benjamin, -- 1738-1820 -- Fiction; Artists -- Juvenile fiction; Quakers -- Juvenile fiction; Cats -- Juvenile fiction; Biographical fiction; Historical fiction